A supply chain resilience model for business continuity: The way forward for highly regulated industries - Aigbogun, Osaro; Xing, M.; Fawehinmi, O.; Ibeabuchi, C.; Ehido, A.; Ahmad, R.B.; Abdullahi, M.S. (2022)
The COVID-19 outbreak is a black swan event that has uncovered the delicateness of global supply chains and business architecture. Underpinned by the agency theory and institutional theory, a proposition for business continuity in the highly regulated pharma industry is presented in this paper. A cross-sectional quantitative study was carried out on a sample of 102 pharma supply chain executives in Malaysia. The primary data were gathered by administering a self-administered questionnaire and analyzed using the partial least squares structural equation modelling (PLS-SEM). The result reveals that supply chain orientation directly influences supply chain resilience. Also, introducing collaborative regulation as a mediator in this relationship shows partial mediation. The notion of collaborative regulation as a behavioral governance mechanism is relatively new, thus, presenting interesting opportunities for further exploration of the subject matter.